2014
DOI: 10.1155/2014/825947
|View full text |Cite
|
Sign up to set email alerts
|

Novel Diagnostic and Therapeutic Techniques for Surveillance of Dysplasia in Patients with Inflammatory Bowel Disease

Abstract: The risk for developing dysplasia and colorectal cancer in patients with longstanding inflammatory bowel disease (IBD) involving the colon is well documented. Random biopsies during white-light, standard-definition colonoscopy (33 to 50 biopsies) with or without dye spraying chromoendoscopy has been the recommended strategy in North America to detect dysplastic lesions in IBD. However, there are several limitations to this approach including poor physician adherence, poor sensitivity, increased procedure time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 74 publications
0
22
0
1
Order By: Relevance
“…However, this is time consuming and often is not followed in clinical practice. 21 In fact, in the current audit, we found that our IBD gastroenterologists took a widely variable number of biopsy specimens in the surveillance group with random biopsies, with 23 median biopsy specimens and a range of 4 to 50 biopsy specimens. This may explain why random biopsies perform less well in the detection of neoplastic lesions compared with targeted biopsies.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…However, this is time consuming and often is not followed in clinical practice. 21 In fact, in the current audit, we found that our IBD gastroenterologists took a widely variable number of biopsy specimens in the surveillance group with random biopsies, with 23 median biopsy specimens and a range of 4 to 50 biopsy specimens. This may explain why random biopsies perform less well in the detection of neoplastic lesions compared with targeted biopsies.…”
Section: Discussionmentioning
confidence: 81%
“…using WLE, HD, VCE, and DCE. 21,25 The details of the techniques and equipment used are shown in Table 2: WLE were standard definition, all others were HD (including HD with white light). The HD endoscopes with electronic filter technology (iSCAN, Tokyo, Japan) may improve the detection and characterization of mucosal and vascular patterns of neoplastic lesions.…”
Section: Surveillance Colonoscopiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The management of circum-DOI: 10.1159/000494409 scribed dysplastic lesions within colitic mucosa should be determined by endoscopic resectability. If the lesion is well circumscribed and can be fully removed, endoscopic resection may be an effective treatment [6][7][8]. Endoscopic treatment preserves the rectum and colon, which results in a better quality of life compared to that after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…(14) CRC risk increases with IBD duration, extent of colonic involvement, prior neoplasia, family history of CRC, and primary sclerosing cholangitis (PSC). (2, 5–7) Accordingly, patients with colonic IBD and these risks are advised to undergo surveillance every 1–3 years(8) by colonoscopy.…”
Section: Introductionmentioning
confidence: 99%